PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA PADA PEMBELIAN ULANG - Erniati, Tri; Yantih, Novi; Widyastuti, Sri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
The development of cosmetic products and increasingly fierce competition between brands make it necessary for cosmetic brands to be able to maintain and increase product purchases by customers. This study aims to provide scientific evidence regarding the influence of brand image, product quality, and price on customer satisfaction and its impact on repurchase of cosmetic skin care products. The method used in this research is descriptive quantitative verification. The research sample consisted of 255 respondents and was analyzed using SEM (Structural Equation Modeling) with LISREL software version 10.2. The results showed that brand image and price have a significant effect on customer satisfaction, while product quality has no significant effect on customer satisfaction. Brand image, product quality, price and customer satisfaction have a significant effect on repurchase of cosmetic skin care products. Brand image and price are the main factors that can influence customer satisfaction, while product quality is not the main consideration that influences customer satisfaction for cosmetic skin care products. Brand image, product quality, price and customer satisfaction are important factors that encourage customers to repurchase cosmetic skin care products.